Understanding Generation Z’s Purchase Decisions for Premium Smartphones: Lifestyle, Financial Constraints, and Brand Image - Nindhita Ajeng Widowati; Iva Sofi Gunawati (Al-Qalam Institue, 2026)
This study investigates the influence of lifestyle, financial constraints, and brand image on premium smartphone purchase decisions among Generation Z students, addressing the paradox of continued purchasing despite limited financial resources. Data were collected from 169 students meeting inclusion criteria and analyzed using Structural Equation Modeling via SmartPLS 4.0 to examine causal relationships among variables. The findings reveal that lifestyle, financial limitations, and brand image simultaneously exert significant positive effects on purchase decisions, with brand image emerging as the most influential factor, while financial limitations do not act as a strong barrier. The results suggest that Generation Z consumers prioritize social identity and lifestyle alignment over financial concerns when making premium purchase decisions. Implications for marketing include the importance of reinforcing brand perception, creating lifestyle-oriented campaigns, and leveraging social recognition as a motivator. These insights provide a more holistic understanding of consumption behavior in digital-native populations and can guide strategies to enhance engagement with young consumers in premium product markets.